Emotional Violence from the Page to the Screen: Moral Abuse and Psychological Manipulation in The Age of Innocence from Edith Wharton to Martin Scorsese - Festa, Beatrice Melodia (Literatūra, 2022)
Martin Scorsese declared that The Age of Innocence is the most violent film he ever made. This contribution aims to examine Scorsese’s representation of emotional violence on screen as opposed to Wharton’s illustration of psychological and emotional abuse in the novel. The essay aims to explore violence in The Age of Innocence, represented both in the novel and in the film as a subtle and crucial theme, so as to examine how Scorsese’s adaptation contrasts with Wharton’s narrative. As such, this interpretation aims to prove how The Age of Innocence stands apart, because of its significance in Scorsese’s career, and how both novel and film go way beyond the conventions of romance by illustrating female emancipation through an exquisite display of moral abuse and psychological manipulation, which Scorsese re-elaborates on screen through a devastating sense of moral frustration. Charting parallels between the novel and the film, the analysis will show how Scorsese re-elaborates a non-graphic form of violence, earlier outlined in the novel by Wharton, through a devastating visual tension. Ultimately, this analysis seeks to offer a reinterpretation of Wharton’s novel through Scorsese’s film adaptation.
Keywords: adaptation; violence; moral abuse; Scorsese; Wharton